Intraoperative ultrasonography-guided surgery: An effective modality for breast conservation after neo-adjuvant chemotherapy - GÜLLÜOĞLU, MAHMUT BAHADIR (WILEY, 2020)
Margin status is one of the significant prognostic factors for recurrence in breast-conserving surgery (BCS). The issue that merits consideration for oncologic safety and cost-effectiveness about the modalities to assure clear margins at initial surgical intervention remains controversial after neo-adjuvant chemotherapy (NAC). The presented study aimed to assess the impact of intraoperative ultrasound (IOUS)-guided surgery on accurate localization of tumor site, adequacy of excision with clear margins, and healthy tissue sacrifice in BCS after NAC. Patients who had IOUS-guided BCS ater NAC were reviewed. No patient had preoperative localization with wire or radiotracer. Intraoperative real-time sonographic localization, sonographic margin assessment during resection, macroscopic and sonographic examination of specimen, and cavity shavings (CS) were done as the standard procedure. No frozen assessment was performed. One hundred ninety-four patients were included, in which 42.5% had pCR. IOUS-guided surgery accomplished successful localization of the targeted lesions in all patients. Per protocol, all inked margins on CS specimens were reported to be tumor-free in permanent histopathology. No re-excision or mastectomy was required. For a setting without CS, the negative predictive value (NPV) of IOUS rate was 96%. IOUS was found to over and underestimate tumor response to NAC both in 2% of patients. IOUS-guided surgery seems to be an efficient modality to perform adequate BCS after NAC with no additional localization method. Especially, when CS is integrated as a standard to BCS, IOUS seems to provide safe surgery for patients with no false negativity and a high rate of NPV.
Keywords: breast-conserving surgery; intraoperative ultrasonography; neo-adjuvant chemotherapy; CONSERVING SURGERY; CANCER PATIENTS; RE-EXCISION; PREOPERATIVE CHEMOTHERAPY; SURGICAL OUTCOMES; ULTRASOUND GUIDANCE; SEED LOCALIZATION; AMERICAN SOCIETY; MARGIN STATUS; MANAGEMENT